“In Honor, as in Limb, Unmarred”: Obsession with the “Whole” Body in Herman Melville’s Battle-Pieces and Aspects of the War - Vanessa Meikle Schulman (European Journal of American Studies)
This article examines Herman Melville’s poetry collection Battle-Pieces and Aspects of the War (1866) using theories and concepts from the sphere of disability studies. Mobilizing evidence from Melville’s letters as well as close readings of the poems, I argue that Melville presented a complicated relationship to questions of bodily wholeness and autonomy in his written work, particularly in response to the political and existential stresses of the U.S. Civil War. Melville conceptualized Battle-Pieces as a chronological archive intended to redeem a narrative of wholeness and overcome a perceived weakness or deficiency in the body politic. However, the book’s fractured arc serves rather to highlight a lack of healing, both political and corporeal. Melville’s obsession with the “whole” body is apparent both in his unpublished, private writing and through close readings of the poems “Donelson,” “The College Colonel,” and others. Reading Battle-Pieces through the lens of disability studies makes visible the author’s conflicted responses to wounded bodies. Melville’s obsession with wholeness and healing was part of a larger national obsession—that of mending the rift between North and South by tending to the physical wounds of individual veterans—a historico-medical context that Melville scholars have largely ignored. Placing Melville’s poems within a larger conversation about medical intervention and the limits of the ‘disabled’ body as a symbol for national regeneration, in this article I show how Melville overtly engaged in ongoing debates about healing and nation-building in the aftermath of the Civil War.